Assessment of Alzheimer’s disease-related biomarkers in patients with obstructive sleep apnea: A systematic review and meta-analysis - Cui, Wenqi; Duan, Zhenghao; Li, Zijian; Feng, Juan (Frontiers in Aging Neuroscience, 2022)
Increasing evidence links Alzheimer’s disease (AD) to various sleep disorders, including obstructive sleep apnea (OSA). The core AD cerebrospinal fluid (CSF) biomarkers including amyloid-β 42 (Aβ42), total tau (t-tau), and phosphorylated tau (p-tau) can reflect key elements of AD pathophysiology before emergence of symptoms. Besides, the amyloid-β (Aβ) and tau burden can also be tested by positron emission tomography (PET) scans. Electronic databases (PubMed, Embase, Web of Science, and The Cochrane Library) were searched until Aug. 2022 to assess the AD-related biomarkers measured by PET scans and CSF in OSA patients. The overall analysis showed significant differences in Aβ42 levels (SMD = -0.93, 95% CI: -1.57 to -0.29, P < 0.001) and t-tau levels (SMD = 0.24, 95% CI: 0.01 to 0.48, P = 0.308) of CSF and Aβ burden (SMD = 0.37, 95% CI= 0.13 to 0.61, P = 0.69) tested by PET scans between the OSA and controls. Furthermore, CSF Aβ42 levels showed significant differences in patients with moderate/severe OSA compared with healthy control and levels of CSF Aβ42 showed differences in OSA patients with normal cognition as well. Besides, age and BMI have influences on the heterogeneity. Our meta-analysis indicated abnormal AD-related biomarkers (CSF and PET scans) in patients with OSA, supporting the current hypothesis that OSA, especially moderate/severe OSA, may start the AD neuropathological process.